(untitled) (Research, Society and Development, 2021)
Deaf education has a vast history of struggles, devaluation and inequalities, but also of many achievements. This work addresses the reality of deaf education during the pandemic. Pointing out how this process of teaching-learning of deaf or hearing impaired students took place, with the use of video classes as the main means of teacher/student interaction. The general objective is to analyze the reality of education for deaf or hearing impaired people in the pandemic scenario in two public schools in the state network of Guaraí. Quali-quantitative research was used as a methodology, collecting data through a questionnaire, aimed at teachers in the regular teaching room and interpreters at the schools targeted by the research. The classes took place mainly through videos that were made available to deaf and hearing students on online platforms. It is important that deaf students are included in the regular classroom, but inclusion cannot be confused with integration. Bilingualism is effective in the teaching-learning process of deaf or hearing-impaired students through active methodologies for better academic performance.